PENDAMPINGAN PSIKOSOSIAL DALAM RANGKA MEMBERIKAN PERLINDUNGAN TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA KEKERASAN SEKSUAL (CONTOH KASUS : PUTUSAN NOMOR 1416/PID.SUS/2018/PN JKT.UTR - Veren Marceline; R Rahaditya (Jurnal Hukum Adigama, 2021)
Children are the next generation of a nation and state in the future whose rights must be protected and even protected. But the fact is that there are still many children who are victims of sexual violence. Children who experience sexual violence have an impact in terms of physical, psychological, and emotional. The term sexual violence is defined as an act that results in death, psychological harm, and deprivation of rights. As a form of protection for children who are victims of sexual violence, protection measures are provided in the form of psychosocial assistance with the aim of restoring the child's social function. So that in this study a problem arises in the form of how to implement psychosocial assistance in order to provide protection for children as victims of criminal acts of sexual violence. The implementation of psychosocial assistance has been regulated in Law Number 35 of 2014 Amendments to Law Number 23 of 2002 concerning Child Protection in Article 69A. However, the fact is that the implementation of psychosocial assistance to child victims of sexual violence is still far from an ideal situation. This happens because in carrying out the implementation of psychosocial assistance there are still several obstacles, so that in carrying out psychosocial assistance to children it becomes hampered. Therefore, the government must pay more attention to and emphasize the rules contained in the Child Protection Act so that they can be socialized in accordance with existing regulations and deal with obstacles that still occur that hinder the implementation of psychosocial assistance to children who are victims of sexual violence.